Resepsi Masyarakat Dullah Utara terhadap Konsep Moderasi Beragama Perspektif Al-Qur’an - Yasin, Rahmah Muharromah (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2022)
This paper aims to describe how the North Dullah community's reception of the concept of religious moderation from the perspective of the Qur'an. This scientific research aims to find out how the wasathiyah verses are based on the viewpoints and assessments of the community in the field. In this study, the area studied has distinctive local wisdom, namely in the North Dullah sub-district, Tual city, which is known as the Larvul Ngabal Customary Law and the Ain ni ain philosophy. The method used in this research is field research with a qualitative research type that produces descriptive data and uses a phenomenological approach. The results in this study are that religious moderation in the reception of the North Dullah community is a moderate religious way, or an inclusive way of Islam or an open religious attitude, not exchanging beliefs, respecting each other in tolerance, peace and justice. In its implementation in the North Dullah sub-district, it is adjusted to local customs, namely the customary law of Larvul Ngabal and the philosophy of Ain ni ain which is the basis. From the results of the interview, the researcher can conclude that in the legal articles of Larvul Ngabal and the philosophy of Ain ni ain it is clear that the customary law and philosophy are in accordance with Islamic Shari'a law, especially the verses regarding moderation.